2017
DOI: 10.5603/kp.a2016.0135
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of valsartan and combination of valsartan and hydrochlorothiazide in the treatment of patients with mild to moderate arterial hypertension — the VICTORY trial

Abstract: A b s t r a c t Background and aim:The aim of the trial was to establish the efficacy and safety of Valsacor ® (valsartan) and Valsacombi ® (combination of valsartan and hydrochlorothiazide) in a wide variety of patient populations with mild to moderate arterial hypertension. Methods:We performed an international, multicentre, open-label, prospective trial. After one week of washout in previously treated patients, the patients were treated for 16 weeks according to the protocol. Naïve patients entered the trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 9 publications
1
4
0
4
Order By: Relevance
“…24 In the same manner, our results are in line with those reported in the VICTORY trial, in which 365 patients were treated with valsartan or a combination of valsartan and HCTZ for 16 weeks; using office BP measurements, the proportion of patients that achieved target BP at the last visit was not significantly different between the two groups (98 vs. 84%, respectively). 25 With respect to the greater reduction in late night and early morning BP, values in chlorthalidone-treated patients (alone and in combination with other agents) are consistent with those reported by Ernst et al, 12 who found a significant reduction in SBP during nighttime hours with chlorthalidone compared to that observed on using HCTZ. Similarly, Pareek et al 13 compared the efficacy of chlorthalidone and two preparations of HCTZ in patients with stage 1 hypertension, and found that compared to the baseline values, all three treatments significantly lowered office BP at weeks 4 and 12; however, at weeks 4 and 12, significant reductions in systolic and diastolic 24-hour ambulatory and nighttime BP were observed with chlorthalidone but not with HCTZ.…”
Section: Discussionsupporting
confidence: 85%
“…24 In the same manner, our results are in line with those reported in the VICTORY trial, in which 365 patients were treated with valsartan or a combination of valsartan and HCTZ for 16 weeks; using office BP measurements, the proportion of patients that achieved target BP at the last visit was not significantly different between the two groups (98 vs. 84%, respectively). 25 With respect to the greater reduction in late night and early morning BP, values in chlorthalidone-treated patients (alone and in combination with other agents) are consistent with those reported by Ernst et al, 12 who found a significant reduction in SBP during nighttime hours with chlorthalidone compared to that observed on using HCTZ. Similarly, Pareek et al 13 compared the efficacy of chlorthalidone and two preparations of HCTZ in patients with stage 1 hypertension, and found that compared to the baseline values, all three treatments significantly lowered office BP at weeks 4 and 12; however, at weeks 4 and 12, significant reductions in systolic and diastolic 24-hour ambulatory and nighttime BP were observed with chlorthalidone but not with HCTZ.…”
Section: Discussionsupporting
confidence: 85%
“…In an international, multicentre, open-label, prospective phase IV trial the efficacy and safety of valsartan or its combination with HCTZ in patients with mild to moderate arterial hypertension was studied. In the VICTORY trial [9], 365 patients from five countries were included. Prior to the start of the active treatment, previously treated patients had to undergo one week of wash-out period.…”
Section: Discussionmentioning
confidence: 99%
“…The duration of the active treatment was 16 weeks [9]. The trial was financially supported by KRKA d. d., Novo mesto, Slovenia.…”
Section: Exclusion Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Czas aktywnego leczenia wynosił 16 tygodni [9]. Firma KRKA d.d., Novo mesto, Słowenia udzieliła wsparcia finansowego w celu realizacji badania.…”
Section: Projekt Badaniaunclassified